ANALISIS MANAJEMEN STRATEGI DALAM MENINGKATKAN DAYA SAING: STUDI MULTI-KASUS DI SEKOLAH MENENGAH ATAS SEDERAJAT DI KECAMATAN DANAU KERINCI - M.Haikal Putra; Ali Marzuki Zebua (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the application of the Balanced Scorecard (BSC) in educational strategy management and its effectiveness in enhancing institutional competitiveness at SMA Negeri 6 Kerinci and MAN 3 Kerinci. The study employs a qualitative approach with a multi-case study design. Data were collected through structured interviews with school/madrasah principals and vice principals, as well as through observation and documentation. Analysis was conducted descriptively based on the four BSC perspectives: financial, customer, internal processes, and learning and growth. The results indicate that SMA Negeri 6 Kerinci has a more integrated BSC implementation, particularly in resource management, promotional strategies, and the use of adaptive learning technologies grounded in interactive pedagogical practices. Conversely, MAN 3 Kerinci demonstrated strengths in religious character development and the development of a web-based digital learning ecosystem that contributes to enhancing teacher professionalism, although it still faces limitations in the areas of promotion, internal coordination, and strategy integration. The novelty of this study lies in the differences in technology integration models within the BSC framework, namely the adaptive-cultural approach at SMA Negeri 6 Kerinci and the centralized digital system at MAN 3 Kerinci, which confirms that the effectiveness of the BSC is determined by the integration of strategies and technological innovation.